Gut Microbiota and Immunoglobulin A Nephropathy: Exploration of Dietary Intervention and Treatment Strategies - Zhaoyang Dong; Ran Zhang; Liang Shen; Hong‐Fang Ji; Haidong He; Xiaoguo Ji; Liming Zhao (2025)
ABSTRACT Immunoglobulin A nephropathy (IgAN) is a primary glomerular disease characterized by the deposition of IgA. The pathogenesis of it is related to the dysbiosis of gut microbiota. Dysbiosis of gut microbiota influences mucosal immune response and systemic immune system, leading to glycosylation‐deficient IgA1 (Gd‐IgA1) increasing, which promotes the development of IgAN. Diet plays an important role in regulating gut microbiota and treating IgAN. In this review, we summarize the interplay between gut microbiota and IgAN, and their underlying mechanisms. We also describe the effects of dietary intake on IgAN, as well as the composition of gut microbiota. The progress on IgAN treatment mainly focuses on inhibiting or regulating the immune system. Moreover, therapeutic strategies related to gut microbiota such as dietary intervention, supplement of probiotics and prebiotics, as well as fecal microbiota transplantation (FMT) have shown the possibility of improving IgAN prognosis. Thus, exploration of the gut‐kidney axis, the long‐term effects of diet and microbiome is necessary to develop more effective treatment strategies.